New Spirituality and Chinese Traditional Thoughts: A Review of Related Literature - Emiliano T. Hudtohan (International Journal of Management and Education in Human Development, 2023)
This narrative is about 21st-century spirituality, anchored to James Ebner's ideas on Human Race Church, Karl Rahner's on Anonymous Christianity, O'Murchu on Quantum Theology, Gordon Lynch's on Progressive Spirituality, Neale Donald Walsch's on The Essential Path, and Joe Dispenza on Becoming Supernatural. These authors' ideas serve as a review of related literature of this narrative on Traditional Chinese Thoughts and 21st Century Spirituality and a theoretical framework for this study. Based on the review of related literature, the following are the findings:1. China as a nation and its citizens qualify to be within the circle of Ebner's Human Race Church and Walsch’s Spiritual Beings Manifesting Physically, and One Essence Manifesting Individuality. 2. The Yin and Yang principle, as the author of life in Chinese cosmology, is aligned with O’Murchu’s declaration that divinity is a vibrant energy. 3. The Chinese Qi or Chi as life energy fuels the life of the cosmos and all of creation, and meta physicist James Ray equates God to Pure Energy. 4. Traditional Chinese Medicine is aligned with Dispenza’s application of meditation for physical health and well-being. 5. Confucianism, which established the rules and rituals of the human relationship with other humans, is a manifestation of the quantum structure of the quark with a big center and many small elements around it. 6. Taoism which defined the relationship of humans with nature, is aligned with Lynch’s New Spirituality which advocates pantheism and panentheism. 7. China embraced the Western dialectic materialism of Karl Marx; it is progressing from a material property and Ecological Civilization to a Socialist Spiritual Civilization.